Valoración pericial psicológica de trastornos mentales en el Ecuador - Izurieta, Juan J. (2021)
In Ecuador, the development of Legal and Forensic Psychology is characterized by being still in development paths, with an obvious gap compared to neighboring countries such as Chile and Colombia. This is due, to a large extent, to the fact that there are countless legal bodies that They urgently need to go through a review with their respective reform that allows a better applicability of the advances achieved in the matter, in addition to facilitating the development of the Legal and Forensic Psychologist.